Exhaustion of CD8+ central memory responder T cell differentiation provokes non-melanoma skin cancer in elderly kidney transplant recipients - Leonhard, Jonas; Schaier, Matthias; Kälble, Florian; Zeier, Martin; Steinborn-Kröhl, Andrea (Frontiers in immunology, 2023)
IntroductionImmunosuppressive therapy prevents graft rejection but increases the risk of non-melanoma skin cancer (NMSC), especially in elderly kidney transplant recipients (KTR).MethodsIn this study, we separately investigated the differentiation of CD8+ regulatory T cells (Tregs) and responder T cells (Tresps) between healthy KTR without NMSC, KTR developing de-novo NMSC within two years after the enrolment, and KTR with NMSC at the time of enrolment. Antigen-unexperienced CCR7+CD45RA+CD31+ recent thymic emigrant (RTE) cells differentiate via CD45RA-CD31+ memory (CD31+ memory) cells, via resting mature naïve (MN) cells or via direct proliferation into CD45RA-CD31- memory (CD31- memory) cells, consisting of both CCR7+CD45RA- central memory (CM) and CCR7-CD45RA- effector memory (EM) cells.ResultsWe found that both RTE Treg and Tresp differentiation via CD31+ memory Tregs/Tresps was age-independently increased in KTR, who developed de novo NMSC during the follow-up period, causing abundant CM Treg/Tresp production, which may be crucial for cancer immunity. These changes favored a strongly increased CD8+ Treg/Tresp ratio, suggesting this ratio as a reliable marker for de-novo NMSC development in KTR. However, with age, this differentiation was replaced by increased conversion of resting MN Tregs/Tresps into CM Tregs/Tresps, which exhausted for Tresps but not for Tregs. In KTR with already existing NMSC at enrolment, differentiation was maintained via conversion and proliferation of resting MN Tregs/Tresps, which however increasingly exhausted with age, especially for Tresps. This resulted in a strong accumulation of terminally differentiated effector memory (TEMRA) Tresps in elderly individuals. Patients with NMSC recurrence showed increased proliferation of resting MN Tregs/Tresps into EM Tregs/Tresps, which tended to exhaust more rapidly, particularly for Tresps, than in patients without NMSC recurrence.DiscussionIn conclusion, we provide evidence that immunosuppressive therapy inhibits differentiation of CD8+ Tregs more than that of CD8+ Tresps, resulting in an exhausted Tresp profile, thus providing a possible therapeutic approach to improve poor cancer immunity in elderly KTR.
Im Titel ist das Pluszeichen bei "CD8+" hochgestellt
Gesehen am 28.06.2023